PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTSN MODEL PADUSUNAN PARIAMAN TAHUN PELAJARAN 2013/2014 - Erawati, Neti; Nasution, Minora Longgom; Haryono, Yulia (Pendidikan Matematika, 2013)
This research is bacground by students understanding of mathematical concepts is low and students more like ask to their friends without attention a question given correct or incorrect. This reseach aims to know how development of understanding indication of mathematical concepts every meeting and what is studentâs understanding of mathematical concepts with apply cooperative learning model the tipe is Think Pair Share with quiz better than studentâs understanding of mathematical concepts with apple conventional learning in the class MTsN Model Padusunan Pariaman 2013-2014 school year. Kind of research is experimental, with planning research toward subject. Population in research is all of students class VIII with class sample VIII2 as class exsperiment and class VIII4 as class control. Instrument in test research understanding mathematical concept in essay with test reliability is r11 = 0,747. technique of data analysis was T-test. Basic result of testing hypotesis obtained P-value = 0,002 more small than of standar obvious that =0,05. So,to get conclusion that understanding mathematical concepts with apply cooperative learning model the tipe is Think Pair Share with quiz better than studentâs understanding of mathematical concepts with apple conventional learning in the class MTsN Model Padusunan Pariaman at the level of 95%.